ANALYSIS OF BASE AND COMPETITIVE COMMODITIES OF CROP SUBSECTOR AND ITS EFFECT ON GDRP GROWTH OF LANGKAT REGENCY - Khalish Khairina; Mrs Fitrawaty (Quantitative Economics Journal, 2020)
Economic Growth is one of indicator which commonly used to observe economic development in a region. Conceptually, economic growth of a region is determined by sector values in producing goods and services. GDRP of Langkat regency is mostly dominated by agriculture, forestry and fisheries sector. Food security that Langkat Regency plan to be achieved really depends on food crops’ supply. However crops’ contribution is decreased every year. Therefore, it’s needed to examine which leading and highly competitive crops’ commodities. This study aimed to determine and analyze a base and competitive crops’ subsector and its effect on GDRP Langkat Regency. LQ was used to determine the base and non base commodities. While the analysis of RCA and MCI were used to see the commodities competitiveness. and to analyse its effect by using Ordinary Least Square. The type of data used was time series since 1996 to 2015 by using Eviews 7.0. Data was obtained from BPS Langkat Regency and Agriculture Department of Langkat Regency. The result of this study showed that paddy, corn, soybean and mungbean were base commodities of crops with average LQ > 1. This study also showed that paddy, corn, soybean and mungbean were highly competitive commodities with average RCA > 1. Average MCI each commodities is > 0,75 showed that commodities trade’s less spread (concentrated). Regression result showed that paddy  has positive effect on GDRP growth in supply side (prob RCA 0,0035 < 0,05). Corn also showed that has positive effect on GDRP growth in supply and demand side (prob RCA 0,0016 < 0,05 and MCI 0,0193 < 0,05). Soybean showed that has positive effect on GDRP growth in production supply (LQ 0,0032 < 0,05) and Mungbean also showed that has positive effect on GDRP growth in production supply (LQ 0,0001 < 0,05).